(6a-5b+c-7d)7=

Simple and best practice solution for (6a-5b+c-7d)7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6a-5b+c-7d)7= equation:


Simplifying
(6a + -5b + c + -7d) * 7 = 0

Reorder the terms for easier multiplication:
7(6a + -5b + c + -7d) = 0
(6a * 7 + -5b * 7 + c * 7 + -7d * 7) = 0
(42a + -35b + 7c + -49d) = 0

Solving
42a + -35b + 7c + -49d = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '35b' to each side of the equation.
42a + -35b + 7c + 35b + -49d = 0 + 35b

Reorder the terms:
42a + -35b + 35b + 7c + -49d = 0 + 35b

Combine like terms: -35b + 35b = 0
42a + 0 + 7c + -49d = 0 + 35b
42a + 7c + -49d = 0 + 35b
Remove the zero:
42a + 7c + -49d = 35b

Add '-7c' to each side of the equation.
42a + 7c + -7c + -49d = 35b + -7c

Combine like terms: 7c + -7c = 0
42a + 0 + -49d = 35b + -7c
42a + -49d = 35b + -7c

Add '49d' to each side of the equation.
42a + -49d + 49d = 35b + -7c + 49d

Combine like terms: -49d + 49d = 0
42a + 0 = 35b + -7c + 49d
42a = 35b + -7c + 49d

Divide each side by '42'.
a = 0.8333333333b + -0.1666666667c + 1.166666667d

Simplifying
a = 0.8333333333b + -0.1666666667c + 1.166666667d

See similar equations:

| 17x-8=12x-13 | | -6y-1=-5y-3 | | 4x-2=-18 | | 5x^2=2-9 | | 1/2y=3 | | b^2+8b+15= | | 2x-3/6-8-x/9=x+3/18 | | 6x12/36 | | 1/6X+2/3 | | 2r^2-2/3r=0 | | (N+9)=3n+27 | | 12.257x+1.9333=281.4 | | 9z-9-2z+2=0 | | y=8x+21.8 | | 6v^2-9=0 | | y=3ac | | 4(X-5/2)^2=49 | | -3(2a-4)+10a=-8 | | x+6/2-5+x/3=2-x/6 | | 2/15X+1/3 | | 4(b+1)-5=4b-1 | | 16=11/12x | | -2500-200x=-4900 | | 4(2m-5)+7m=25 | | x*x+6x-7=0 | | -60/4 | | 9ln(4x)=36 | | 2(X+9)/3=X-8 | | s/-51=-459 | | 12x-19=77 | | 12x-6(x+5)=18 | | 18+16+6y-y=80-1 |

Equations solver categories